Optimalisasi Efisiensi Logistik Maritim: Peran Manajemen Pelabuhan dan Strategi Mengatasi Hambatan Pabean Dalam Meningkatkan Ekspor Impor Indonesia - Ariyani, Danisha (Peneliti.net, 2025)
This study aims to analyze and optimize maritime logistics efficiency in Indonesia, focusing onthe role of port management and strategies to overcome customs barriers. Maritime logisticsis a vital component of the global trade system, especially for an archipelago nation likeIndonesia, which heavily relies on sea transportation for exports and imports. However,challenges such as suboptimal port management and prolonged customs barriers c ihan hindermaritime logistics efficiency.Effective port management plays a crucial role in reducing vessel waiting times, speeding uploading and unloading processes, and enhancing port capacity. This study examines variousport management approaches, including the use of information technology, human resourcetraining, and collaboration among port stakeholders. Additionally, the study highlights theimportance of transparency and simplification of customs procedures as key strategies toovercome customs barriers. Customs barriers often cause shipment delays and increasedlogistics costs, ultimately negatively impacting Indonesia’s export-import competitiveness inthe global market. Optimizing maritime logistics efficiency through effective port managementand strategies to reduce customs barriers is key to enhancing Indonesia’s export-importperformance. The practical recommendations from this study are expected to assistpolicymakers and industry practitioners in formulating more effective policies and strategiesto boost Indonesia’s maritime competitiveness on the international stage.